ANALISIS PENGGUNAAN SMCP (STANDARD MARINE COMMUNICATION PHRASES) DALAM MENUNJANG KOMUNIKASI ANTAR KAPAL DAN DENGAN OPERATOR VTS (VESSEL TRAFFIC SERVICE) DI KMP. PORTLINK III. - Muhammad Julian Delon; Achmad Ali Mashartanto; Rizal Rochmansyah; Naf'an Arifian; Bhima Siswo P (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze and optimize the use of SMCP (Standard Marine Communication Phrases) to support communication between vessels and with the Vessel Traffic Service (VTS) on KMP Portlink III. The study used a qualitative approach using observation, interviews, and documentation during sea practice. The results indicate that the implementation of SMCP on board is not yet fully optimal. There is still the use of general English, a lack of consistency in standard phrase structures, and minimal ongoing evaluation and training. Inhibiting factors include Man, Method, Machine, Material, Measurement, and Mother Nature, such as non-standard communication habits, limited proficiency in maritime English, and lack of supervision during watch duty. This impact has the potential to lead to miscommunication, especially when ships enter VTS areas with heavy traffic. Recommended optimization efforts include increasing knowledge accompanied by routine SMCP training, briefings before and after watch shifts, and active supervision from leaders and senior officers. Regarding inhibiting factors beyond human control, such as lighting short circuits caused by bad weather, port authorities or shore officials must be more prepared and responsive in improving the quality and quantity of lighting units. With consistent SMCP implementation in accordance with IMO standards, navigational communications can be clearer, more structured, and more effective, thereby enhancing navigational safety.